Structure–performance evolution mechanism of the wear failure process of coated spherical plain bearings. (May 2022) - Liu, Yunfan; Ma, Guozheng; Zhu, Lina; Wang, Huipeng; Han, Cuihong; Li, Zhen; Wang, Haidou; Yong, Qingsong; Huang, Yanfei
Highlights: The variation trend of the torque was closely related to the evolution of the bearing contact surfaces. The smooth area was an important reason the bearing maintained stable operation for a long time. Plastic deformation promoted the evolution of broken areas to smooth areas of coating surfaces. The change of friction pair and the accumulation of damage led to torque mutation. Wear failure mechanisms of bearings included plastic deformation, abrasive wear and adhesive wear, and oxidation wear. Abstract: The spherical plain bearing is an important basic moving component which is widely used in aerospace and industrial equipment. However, current studies are predominantly conducted on gasket-type bearings, with only a few on the failure behaviour and mechanism of the coated spherical plain bearing. In the present work, the wear failure behavior of GE17ES coated spherical plain bearings is investigated using the whole life and stage life test methods. Furthermore, the mapping relationship between the macroscopic torque change and the micro-structure evolution of the bearing friction surface in each life stage is analyzed using the microscopic characterization method. The results indicate that the torque signal can reflect the service state of the bearing comprehensively. More specifically, during the normal service stage, the smooth area of the coating ensures the stable operation of the bearing. Conversely, during the signal mutation stage, the accumulation of damage on the substrate surface causes rapid failure of the bearing. In summary, the main wear failure mechanism of the bearing includes plastic deformation, abrasive wear and adhesive wear, and oxidation wear may accelerate its failure. These results revealing the damage and failure evolution process of the coated spherical plain bearing, could provide a theoretical reference for future studies on the wear failure of coated spherical plain bearing.